Pengaruh Disiplin dan Motivasi Kerja Kepala Sekolah dalam Meningkatkan Kualitas Lembaga Pendidikan Islam - Febia Ghina Tsuraya; Hasyim Asy’ari; Siska Maulidya; Ulfa Nur Fajariya (Al-Munawwarah : Jurnal Pendidikan Islam, 2023)
Currently, there are still many teachers who teach lack motivation, discipline and maximum performance in carrying out their duties. So it has a negative impact on the quality of graduation and the quality of education. This is a big challenge for school principals in their leadership. Therefore this study aims to describe and examine the "Influence of Work Discipline and Work Motivation Applied by Principals in Improving the Quality of Educational Institutions". The methods used in this research study were interviews and library research. The literature review is a study that refers to journals, books, and journals related to research studies designated as the main source. Results and Discussion of this study explain the meaning of work discipline, work motivation, and the influence of work discipline and work motivation applied by the Principal. Applying Work Discipline and Work Motivation is expected to improve the quality of effective educational institutions.